2022
DOI: 10.5348/100049d05mc2020ra
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sleep in patients with hypermobile Ehlers–Danlos syndrome and patients with generalized hypermobility spectrum disorder

Abstract: Aims: Research objectively evaluating physical activity (PA) and sleep in adults with hypermobile Ehlers-Danlos syndrome (hEDS) and generalized hypermobility spectrum disorder (G-HSD) is lacking. Furthermore, it is not clear to what extent frequently occurring symptoms in these patients are related to their PA and sleep. Therefore, a cross-sectional study was performed to objectively evaluate, and identify factors contributing to, PA and sleep in adults with hEDS and G-HSD.Methods: Twenty female adults with hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…As hypothesized, this study found no significant different body composition and bone parameters between individuals with hEDS and G-HSD. These findings confirm previous studies of our research group [3,13,21] and the studies of Copetti et al [22] and Hakim et al [23], showing no differences in symptoms and comorbidities between these two patient groups. Therefore, we once again suggest a supplementary classification, which classifies patients according to their comorbidities and symptoms, and which may better guide health practitioners in their clinical decisions [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As hypothesized, this study found no significant different body composition and bone parameters between individuals with hEDS and G-HSD. These findings confirm previous studies of our research group [3,13,21] and the studies of Copetti et al [22] and Hakim et al [23], showing no differences in symptoms and comorbidities between these two patient groups. Therefore, we once again suggest a supplementary classification, which classifies patients according to their comorbidities and symptoms, and which may better guide health practitioners in their clinical decisions [21].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, due to higher risk of falling because of impaired balance, coordination and gait, and fear of (sub)luxating joints, it may be hypothesized that individuals with hEDS and G-HSD, avoid potential highrisk situations [17]. Accordingly, a previous study of our research group showed higher levels of kinesiophobia in individuals with hEDS and G-HSD [3].…”
Section: Tablementioning
confidence: 79%
See 1 more Smart Citation